2013
DOI: 10.1075/sic.10.3.05mic
|View full text |Cite
|
Sign up to set email alerts
|

Voiceless stop aspiration in Yucatan Spanish

Abstract: Previous research has indicated that in Yucatan Spanish, /ptk/ are aspirated at greater levels than in other varieties, a feature attributed to contact with Yucatec Maya, a language that has both aspirated and ejective voiceless stops. The current study presents the first quantitative, acoustic, variationist investigation of the linguistic and social factors that constrain aspiration (as measured by VOT) in Yucatan Spanish. Analyses, conducted using mixed-effects statistical models, indicate that VOT values ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In the present data, most speakers show cases of glottal insertion, but some -specifically older speakers and Maya speakers -show much higher rates. Recall also that García Fajardo (1984) did not observe important differences across age groups, further suggesting that standardization of this feature is a recent process in YS, as also found by studies of other traditional variables in YS (Michnowicz, 2011(Michnowicz, , 2012Michnowicz & Carpenter, 2013).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In the present data, most speakers show cases of glottal insertion, but some -specifically older speakers and Maya speakers -show much higher rates. Recall also that García Fajardo (1984) did not observe important differences across age groups, further suggesting that standardization of this feature is a recent process in YS, as also found by studies of other traditional variables in YS (Michnowicz, 2011(Michnowicz, , 2012Michnowicz & Carpenter, 2013).…”
Section: Discussionmentioning
confidence: 53%
“…In sum, this study has shown that glottal insertion in YS is governed by both linguistic and extra-linguistic factors, is almost certainly a contact-feature in this dialect, and is quickly disappearing from the speech of younger speakers of both Spanish and Maya backgrounds. Increased access to formal education was identified as one of the primary factors driving this move to a more 'standard' variety of Spanish, as has also been documented for other features of YS (Michnowicz, 2011;Michnowicz & Carpenter, 2013). Future study should examine this feature in the speech of children and adolescents in order to shed further light on the role of education and dialect contact in the overall standardization of Yucatan Spanish.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…"The cat with red boots ate a mouse, not the one with blue boots." (Zubizarreta 1999, p. 4230) of voiceless plosives (Lope Blanch 1987;Mediz Bolio 1951;Michnowicz and Carpenter 2013;Suárez Molina 1996), or glottalization (Lope Blanch 1987;Michnowicz and Kagan 2016;Suárez Molina 1996), and it is especially true for the peculiar intonation of the variety (see, e.g., Barrera Vásquez 1977;Mediz Bolio 1951;Michnowicz and Barnes 2013;Suárez Molina 1996):…”
mentioning
confidence: 99%